Comparison of steam injected diesel engine and Miller cycled diesel engine by using two zone combustion model - Gonca, Guven; Sahin, Bahri; Ust, Yasin; Parlak, Adnan; Safa, Aykut (ELSEVIER SCI LTD, 2015)
Emissions, especially NOx, released from diesel engines must be decreased to limit values described by the regulations because emissions have many bad effects on the environment. One of the known methods for reduction NOx emissions is to apply Miller Cycle to a diesel engine. In this study, Miller cycle is carried out by lowering the compression ratio according to the expansion ratio with closing the intake valve 30 degrees crank angle later from the BDC (Bottom Dead Center) compared to standard diesel engine. Another method used is steam injection into diesel engine to decrease NOx emissions. And also, this method could be used to improve the performance and efficiency. Because of these positive effects, Miller cycle and steam injection methods could be implemented into diesel engines together. In this paper, Miller cycled diesel engine with steam injection has been modeled by using zero-dimensional two-zone combustion model. The obtained results have been compared with conventional diesel engine, Miller Cycled diesel engine and steam injected diesel engine in terms of performance and NO emissions. In the results, Miller Cycled diesel engine with steam injection is more efficient at low and medium engine speeds and has less NO emissions than conventional diesel engine, steam injected diesel engine and Miller Cycled diesel engine in all conditions. (C) 2014 Energy Institute. Published by Elsevier Ltd. All rights reserved.
Keywords: Miller cycle; Engine performance; Diesel engine; Steam injection; NOx; PERFORMANCE ANALYSIS; NOX EMISSION; HEAT-ENGINE; EFFICIENCY; Energy & Fuels